A Bloody Mess: An Unusual Case of Diffuse Alveolar Hemorrhage Because of Warfarin Overdose. (September 2016) - Heffler, Enrico; Campisi, Raffaele; Ferri, Sebastian; Crimi, Nunzio
Abstract : We herein present the case of a patient with frank hemoptysis and hematuria, dyspnea, and cough. The patient was known to be affected by Chronic Obstructive Pulmonary Disease (COPD) and dilated cardiomyopathy with atrial fibrillation. For this latter condition, he was supposed to take 1.25 mg warfarin daily. Laboratory findings revealed very high levels of International Normalized Ratio (INR) (16), and the patient referred that he self-increased warfarin dose to 5 mg daily since 8 days before the onset of symptoms. Computed tomography scan revealed diffuse bilateral signs of alveolar hemorrhage with hydroaerial levels within emphysematous cysts. Wafarin was immediately stopped and changed with 220 mg dabigatran daily, and he was properly treated to restore a normal coagulation status. We concluded for a case of diffuse alveolar hemorrhage because of warfarin overdose.